Perspektiva študentov zdravstvene nege do istospolno usmerjenih - Šavli, Danijela (Obzornik zdravstvene nege, 2019)
Introduction: Homosexuals continue to face unequal treatment within the healthcare system. The purpose of the research was to determine nursing students' knowledge and attitudes towards homosexuals. Methods: A non-experimental quantitative descriptive research study used the following questionnaires translated into Slovene: The Sex Education and Knowledge about Homosexuality (Cronbach % = 0.97) and The Attitudes Towards Homosexuals (Cronbach % = 0.95). 70 undergraduate students of Nursing were included in the study. Data were collected via an online questionnaire from June to August 2018 and were analysed with descriptive statistics: the Mann-Whitney U test, Kruskal Wallis H test, Linear regression and X2 test. P-value % 0.05 was considered significant. Results: Students have shown insufficient knowledge about homosexuality since from a total of 32 questions, they only answered 6 questions correctly. Findings have shown that a positive attitude towards homosexuality is shown by male students (p < 0.05), students aged 28 to 37 years, married students, students who identified themselves as Catholic and students in the third year of their studies. However, the differences in attitudes among the students were not statistically significant (p % 0.05). Discussion and conclusion: Research has shown that nursing students lack the knowledge about homosexuality and have a negative attitude towards homosexuality. To achieve equal treatment for all patients, an inclusion of cultural competences in the Nursing curriculum is necessary.
Keywords: attitudes; cultural competences; homoseksualnost; homosexuality; knowledge; kulturne kompetence; nursing students; stališča; študenti zdravstvene nege; zdravstvena nega; znanje